Serum prolidase activity, oxidative stress, and antioxidant enzyme levels in patients with prostate cancer - Kaba, Mehmet; Pirincci, Necip; Demir, Halit; Verep, Samed (Elsevier Science Inc, 2024)
Objectives: We aimed to identify serum prolidase activity, oxidative stress, and antioxidant enzyme levels in patients with prostate cancers and to evaluate their relationships with each other. Materials and methods: A total of 34 male patients with prostate cancer and with a mean age of 64.2 +/- 4.4 were included in the study. The control group comprising 36 male patients (mean age 61.2 +/- 3.4) was randomly selected among the volunteers. Serum samples for measurement of superoxide dismutase (SOD), glutathione peroxidase (GPx), Catalase (CAT), malondialdehyde (MDA), glutathione (GSH), and prolidase levels were kept at -20 & ring;C until they were used. Results: Serum prolidase activity and MDA levels were significantly higher in prostate cancer patients than in controls (all, P < 0.05), while SOD, GPx, and CAT levels were significantly lower (P < 0.05). Conclusion: Our results indicate that increased prolidase seems to be related to increased oxidative stress along with decreased antioxidant levels in prostate cancer. (c) 2024 Elsevier Inc. All rights reserved.
Keywords: Prostate cancer; Prolidase activity; Antioxidant enzyme